Induction furnace - a universal metallurgical unit for solid-phase reduction and melting of steel and high-carbon ferromanganese - Grek , O.S.; Velychko , K.O. (Theory and Practice of Metallurgy, 2023)
A method of solid-phase reduction of iron and manganese oxides and melting of steel and ferromanganese in an induction furnace is proposed. The scheme of the process of reduction of iron and manganese oxides is presented. It is proposed to use pellets (briquettes) consisting of a mixture of ore-coal component and iron-containing material as charge materials, or ferromanganese-ore-coal pellets (briquettes) in the case of manganese oxides reduction. The mechanism of heating of such pellets (briquettes) in an induction furnace is considered and the capabilities of the method are experimentally verified. The high efficiency of solid-phase reduction and melting of steel and ferromanganese in laboratory and industrial induction furnaces is shown.